Could someone show me how to solve this? Hope I write this correctly. the -5/2x and the 5/6x are fractions.

Find the input value for which the functions f(x)= -5/2x+2 and g(x)= 5/6x-4 have the same output value.

Could someone show me how to solve this? Hope I write this correctly. the -5/2x and the 5/6x are fractions.

Find the input value for which the functions f(x)= -5/2x+2 and g(x)= 5/6x-4 have the same output value.

Find the input value for which the functions f(x)= -5/2x+2 and g(x)= 5/6x-4 have the same output value.

- stapel_eliz
**Posts:**1670**Joined:**Mon Dec 08, 2008 4:22 pm-
**Contact:**

zellm wrote:Find the input value for which the functions f(x)= -5/2x+2 and g(x)= 5/6x-4 have the same output value.

If the function values are the same for some value of x, then set the function expressions equal and solve for that value of x.

Does this help any? This is a sample question for an exam.

Find the input value for which the functions f(x)= (-5/2)x+2 and g(x)= (5/6)x-4 have the same output value.

Find the input value for which the functions f(x)= (-5/2)x+2 and g(x)= (5/6)x-4 have the same output value.

- stapel_eliz
**Posts:**1670**Joined:**Mon Dec 08, 2008 4:22 pm-
**Contact:**

zellm wrote:Does this help any?

Find the input value for which the functions f(x)= (-5/2)x+2 and g(x)= (5/6)x-4 have the same output value.

Ah. That would

To find the input value "x" that makes the output expressions "-(5/2)x + 2" and "(5/6)x - 4" equal to each other, follow the instructions provided earlier: Set the output expression equal to each other:

. . . . .-(5/2)x + 2 = (5/6)x - 4

...and

A good first step might be to multiply through by 6, thus getting rid of the denominators.

. . . . .-15x + 12 = 5x - 24

...etc, etc, and so forth.